A Workshop on Disaster Risk Reduction and Risk Transfer : Toward Concrete Action in South Asia and East Asia and the Pacific - World Bank (Washington, DC, 2013)
This is a summary report of the South Asia Region and the East Asia Pacific regions training workshop from April 28-30, 2008 on the importance of disaster risk reduction and risk transfer including major concepts, models, and various applications of disaster risk reduction around the globe. This report represents an analysis and summary of the main presentations made during the course of the workshop. It provides a comprehensive assessment of the major points of discussion and an overview of the salient issues that emerged during the event. Specific policy recommendations are also outlined here which will serve as an important instrument for relevant Bank projects and client governments facing issues of how to mainstream disaster risk reduction practices into development initiatives.